2009
DOI: 10.1016/j.mcm.2009.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Vibration of a Reissner–Mindlin–Timoshenko plate–beam system

Abstract: In this paper, we consider a plate-beam system in which the Reissner-Mindlin plate model is combined with the Timoshenko beam model. Natural frequencies and vibration modes for the system are calculated using the finite element method. The interface conditions at the contact between the plate and beams are discussed in some detail. The impact of regularity on the enforcement of certain interface conditions is an important feature of the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The theories are characterised by an equivalent approximation degree known as the Reissner–Mindlin plate theory. Their comparison is discussed in [ 5 , 6 , 7 , 8 ], etc. Theoretical considerations can be found in [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] for higher-order shear deformation theories as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theories are characterised by an equivalent approximation degree known as the Reissner–Mindlin plate theory. Their comparison is discussed in [ 5 , 6 , 7 , 8 ], etc. Theoretical considerations can be found in [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ] for higher-order shear deformation theories as well.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 6 ], for Reissner, Mindlin and Reddy plate models, a solution to the rectangular transverse plate sinusoidally loaded and freely supported along all the edges is given. Vibrations in the plate–beam system, in which the Reissner–Mindlin plate model related to the Timoshenko beam model was applied, were analysed in [ 7 ]. In [ 11 , 16 ], it is shown that when the plate thickness is around zero, the solution for the Reissner–Mindlin plate becomes close to the solution within the Kirchhoff–Love plate theory (the so-called classical plate theory (CPT)).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies concerning dynamic analysis of plates on elastic foundation are performed. Labuschange et al [2] analyzed a plate-beam system in which Reissner-Mindlin plate model is combined with the Timoshenko beam model, and calculated natural frequencies and vibration modes for the system. Sapountzakis and Katsikadelis [3] presented an optimized model for the analysis of plates reinforced with beams.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied the free vibration for Mindlin plates [8][9][10][11][12][13][14][15][16][17][18][19][20]. Liew et al [9] used the boundary characteristic orthogonal polynomials to approximate the transverse displacement and rotational functions of Mindlin plates.…”
mentioning
confidence: 99%
“…Although much attention has been paid to the free vibration [8][9][10][11][12][13][14][15][16][17][18][19][20] and response in time domain [21,22] for Mindlin plates, few researchers have studied the dynamic response in frequency domain for finite Mindlin plates. Previous works on the vibratory power flow in finite Mindlin plates show that the shear and rotary inertia corrections only influence the power flow at high frequencies [30][31][32].…”
mentioning
confidence: 99%